Multinationals and development in Black Africa : a case study in the Ivory Coast - Masini, Jean.; Ikonicoff, Moises; Jedlicki, Claudio; Lanzarotti, Mario (Farnborough, Eng. : Saxon House, European Centre for Study and Information on Multinational Corporations, 1979)
This book examines the role of multinational corporations in development of Africa with specific reference to Ivory Coast.
Translation of Les multinationales et le développement.
Includes bibliographical references.
lje 19/01/2018
Loans
Keywords: International business enterprises; Industries; Ivory Coast